2013
DOI: 10.1016/j.hrthm.2013.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Terminating ventricular tachyarrhythmias using far-field low-voltage stimuli: Mechanisms and delivery protocols

Abstract: Background Low-voltage termination of VT and atrial fibrillation has shown promising results, however the mechanisms and full range of applications remain unexplored. Objective This study aimed to elucidate the mechanisms for low-voltage cardioversion and defibrillation, and to develop an optimal low-voltage defibrillation protocol. Methods We developed a detailed MRI-based computational model of the rabbit right ventricular wall. We applied multiple low-voltage far-field stimuli of various strengths (≤1 V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 22 publications
2
65
0
Order By: Relevance
“…Such a choice of pacing frequency allows for an efficient scanning of the phase of the vortex in order to find the vulnerable window for vortex termination 27,28 . A simulation study in a realistic three-dimensional cardiac geometry demonstrated for selected examples that LEAP works for a pacing period of 88% of the VF cycle length, but often fails for much faster pacing with a period of 16% of the VF cycle length 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Such a choice of pacing frequency allows for an efficient scanning of the phase of the vortex in order to find the vulnerable window for vortex termination 27,28 . A simulation study in a realistic three-dimensional cardiac geometry demonstrated for selected examples that LEAP works for a pacing period of 88% of the VF cycle length, but often fails for much faster pacing with a period of 16% of the VF cycle length 29 .…”
Section: Introductionmentioning
confidence: 99%
“…At that time, an accurate representation of cardiac tissue in terms of the representation of individual cells was inconceivable for reasons of both storage and computing time. This has changed dramatically; in recent computational studies, 29 million computational nodes were used to represent cardiac tissue [27,47]. The computational mesh size in these simulations was about 59 µm, which should be compared with 100 µm, the typical length of a cardiac cell.…”
Section: Available Computational Power Allows For Cell Size Resolutionmentioning
confidence: 99%
“…The numerical accuracy of the discretizations considered was assessed using a single-cell problem (24)(25)(26)(27)(28)(29)(30) and the method of manufactured solutions. As seen in Tables 2-4, all the discretizations provide converging numerical solutions.…”
Section: Numerical Accuracymentioning
confidence: 99%
See 1 more Smart Citation
“…The recent simulation study by Rantner at al. [97] aimed to elucidate these mechanisms and to develop an optimal low-voltage defibrillation protocol. Based on the simulation results using a complex high-resolution MRI-based ventricular wall model, a novel two-stage low-voltage defibrillation protocol was proposed that did not involve the delivery of the stimuli at a constant cycle length.…”
Section: Model-based Innovation To Improve Arrhythmia Termination By mentioning
confidence: 99%